Genetic assessment of subspecies composition in bean goose (Anser fabalis) harvest in Sweden, Finland and Estonia - Honka, Johanna; de Jong, Adriaan; Jumppanen, Erika; Alhainen, Mikko; Piironen, Antti (SPRINGER, 2025)
Bean goose (Anser fabalis) harvest in Europe consists of two subspecies, whose conservation statuses are different. However, the proportions of each subspecies in hunting bags are unknown. We studied the subspecies composition among harvested bean geese in Sweden, Finland and Estonia by sequencing a short mitochondrial DNA (mtDNA) region (210 bp). The proportion of taiga bean geese (A. f. fabalis) over two hunting seasons was 94% in Sweden, but only 5.8% and 11% in Estonia and southeastern Finland, respectively. The majority of harvested bean geese in Estonia and southeastern Finland were tundra bean geese (A. f. rossicus), and hence the results show that the Finnish spatio-temporal harvest regulations have successfully managed to focus the harvest mostly to the abundant tundra bean goose. We also detected mitochondrial heteroplasmy, i.e. multiple mtDNA variants within some of the individuals. In addition, we discovered a few exceptional individuals with an mtDNA haplotype belonging to eastern taiga bean goose (A. f. middendorffii) or greater white-fronted goose (A. albifrons), which could be hybrids between bean goose subspecies or interspecific hybrids. Hybrid individuals are a problem to this type of method. We also noted that it was not possible to distinguish bean geese and pink-footed goose (A. brachyrhynchus). Our derived method is more cost-efficient than previously used molecular methods, and could be used to monitor bean goose hunting bag in the future.